Integritas Rasuli Sebagai Apologetika Gaya Hidup - Mona, Peter Sys Prayuda (Shalom: Jurnal Teologi Kristen, 2026)
This article presents a deep theological and practical analysis of the relevance of the leadership and service model of the Apostle Paul, as recorded in Acts 20:17–38, as a fundamental apologetic response to the crisis of truth in the digital era. Amidst the onslaught of the post-truth phenomenon, the proliferation of disinformation (hoaxes), and the erosion of public trust in religious institutions in Indonesia, the Church faces an unprecedented credibility challenge. This research employs a qualitative method with a historical-grammatical exegesis approach to the text of Paul's farewell address in Miletus, which is then critically dialogued with the sociological realities of the digital society and the principles of national insight (Wawasan Kebangsaan). The findings indicate that Paul’s model of ministry characterized by lifestyle integrity (transparency of life), economic independence through the tentmaking work ethic, authentic humility (tapeinophrosynē), and the courage to proclaim the "whole purpose of God" is not merely a historical record but the most relevant apologetic framework for the present time. Apologetics in the digital age can no longer rely solely on propositional arguments but demands the incarnation of verifiable truth values in public life. This model offers an ethical foundation for Christians to contribute to nation-building through healthy digital participation, rejection of polarization, and the maintenance of national unity, in alignment with the mandate to seek the welfare of the city.